2010
DOI: 10.1136/bjsm.2010.078725.147
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of nutritional supplements in gyms

Abstract: The abuse of all types of supplements to improve sport performance and physical fi tness has spread to regularly gym users. The most appealing supplements are those that claim to help build muscle, improve endurance and reduce body fat. The aim of this study to evaluate the intake of nutritional and dietary supplements among males from four gyms in Kurukshetra, Haryana (India). Two hundred and seventy-three users of above 16 years completed a self-administered questionnaire that had been pilot-tested to ensure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…The use of dietary supplements has been steadily increasing in developing countries (Gahche et al, 2011). An Indian study (Malik and Malik, 2010) reported that gym goers using dietary supplements to increase muscle mass and decrease body fats were unaware of their possible side effects. Hydroxycut is a herbal preparation marketed as an aid for weight loss.…”
Section: To the Editormentioning
confidence: 99%
“…The use of dietary supplements has been steadily increasing in developing countries (Gahche et al, 2011). An Indian study (Malik and Malik, 2010) reported that gym goers using dietary supplements to increase muscle mass and decrease body fats were unaware of their possible side effects. Hydroxycut is a herbal preparation marketed as an aid for weight loss.…”
Section: To the Editormentioning
confidence: 99%
“…The other nutritional supplements of vitamins, minerals, and botanical products used by gym goers have been reported in previous (Barnes, et al, 2007;Espinoza et al, 2018;Foote et al, 2003;Jawadi, et al, 2017;O'Brien, et al, 2017;Ruano & Teixeira 2020). Indeed, Malik (2017) had reported that 14 different supplements were used by gym goers and it is possible that the gym goers could be using a combination of nutritional supplements.…”
Section: Discussionmentioning
confidence: 86%
“…11 Although there are data to support the potential craving for sports drinks, caffeine, and creatine, most of the alleged nutritional supplements have not been defended or verified by scientific studies that they boost athletic performances. 12 Inappropriate uses of these products or contamination may cause possible health issues, and athletes may be at risk of violating anti-doping regulations. 12,13 The usage rate of various nutritional supplements and hormones has publicly been reported worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…12 Inappropriate uses of these products or contamination may cause possible health issues, and athletes may be at risk of violating anti-doping regulations. 12,13 The usage rate of various nutritional supplements and hormones has publicly been reported worldwide. However, there are scant published data on the general use of these fitness products by the members of the gym in Sulaymaniyah, the Kurdistan Region's intellectual capital.…”
Section: Introductionmentioning
confidence: 99%